ANALISA FISIK FORTIFIKASI BUBUR INSTAN LABU KUNING DAN IKAN LELE SANGKURIANG (Clarias gariepinus) SEBAGAI MAKANAN PENDAMPING AIR SUSU IBU: Effect of Rasio Rehydration on the Substitution of Pumpkin Flour and Catfish Flour on the Physical Characteristics of InstantBaby Porridge - Qodriyah, Nur Latifatul; Nur Latifatul Qodriyah; Mirriyadhil Jannah; Lita Meilina (Universitas Bumigora, 2025)
Complementary feeding (MP-ASI) plays an important role in providing the nutritional intake of infants past the age of 6 months in the form of instant baby porridge. Some instant porridge on the market still use rice and fruit as the main ingredients but the utilization of pumpkin and catfish as the main ingredients is still limited. This study aims to increase the nutritional content of the product using pumpkin and catfish. The rehydration ratio is thought to affect the physical characteristics of the porridge and may affect its nutritional value. The method used in this study was the Complete Randomized Design (CRD) experimental method. This study used 4 different rehydration ratio comparisons between porridge and water. The best rehydration ratio will be further tested on porridge particle size parameters. The results showed that the best rehydration ratio was in treatment R2 with a porridge-to-water ratio of 1:1.5. The physical analysis of instant pumpkin and catfish porridge included a density of 0.65 g/mL, solubility of 6.5%, and water absorption capacity of 5.2 g/g, which met the standards for commercial instant porridge for complementary feeding. Proper rehydration treatment in the fortification of yellow squash flour and catfish flour as the main ingredients for instant porridge production can maximize the nutritional content of the instant porridge that will be consumed.